2009
DOI: 10.1590/s0066-782x2009001000011
|View full text |Cite
|
Sign up to set email alerts
|

O eletrocardiograma no diagnóstico da hipertrofia ventricular de pacientes com doença renal crônica

Abstract: ECG is a useful, efficient, and highly reproducible method for the diagnosis of LVH in HD patients. In this population, the Cornell-product proved to be the most reliable criterion for the detection of LVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Costa et al 26 , studying patients with chronic kidney disease stage 5, whose prevalence of LVH was 83% and mean LVMI of 154.9 ± 57.3 g/m 2 , also showed that the Sokolow-Lyon voltage, Sokolow-Lyon product, Cornell voltage, Cornell product and Romhilt-Estes criteria diagnosed more LVH in the male population.…”
Section: Colosimo Et Al Ecg: Lvh Degree and Gendermentioning
confidence: 92%
“…Costa et al 26 , studying patients with chronic kidney disease stage 5, whose prevalence of LVH was 83% and mean LVMI of 154.9 ± 57.3 g/m 2 , also showed that the Sokolow-Lyon voltage, Sokolow-Lyon product, Cornell voltage, Cornell product and Romhilt-Estes criteria diagnosed more LVH in the male population.…”
Section: Colosimo Et Al Ecg: Lvh Degree and Gendermentioning
confidence: 92%
“…5 O ecocardiograma e o eletrocardiograma são exames úteis na avaliação da DCV dos urêmicos. 6 Já a ultrassonografia com Doppler permite estudar a estrutura e funções das artérias em humanos. Assim, aumento da espessura da camada íntima-média da artéria carótida comum está relacionada aos fatores de risco cardiovasculares tradicionais, prediz a probabilidade de eventos cardiovasculares e cerebrovasculares em certas populações, e prediz a gravidade e a extensão da doença coronariana.…”
Section: Introductionunclassified